2015
DOI: 10.1111/aos.12805
|View full text |Cite
|
Sign up to set email alerts
|

Bleb‐related infection revisited: a literature review

Abstract: ABSTRACT. Bleb-related infection (BRI) is one of the serious complications of glaucoma filtering surgery. This literature review is aimed at the evaluation of recent studies related to BRI. The review presented and discussed risk factors, and clinical and laboratory diagnosis emphasizing advances in diagnostic techniques to detect and distinguish the disease as well as to initiate immediate intensive antibacterial treatment. Clinical features of recognized prognostic factors of visual outcome were also present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 101 publications
(170 reference statements)
2
44
0
4
Order By: Relevance
“…Bleb‐related infection was not identified as a risk factor in this study, although previous studies reported bleb‐related infection resulted in visual acuity loss (Yassin ) and our multicentre prospective observational study, the Japan Glaucoma Society Survey of Bleb‐related Infection study, reported that bleb‐related infection, particularly stage III, causes significant visual impairment (Yamamoto et al. ,b).…”
Section: Discussionmentioning
confidence: 53%
“…Bleb‐related infection was not identified as a risk factor in this study, although previous studies reported bleb‐related infection resulted in visual acuity loss (Yassin ) and our multicentre prospective observational study, the Japan Glaucoma Society Survey of Bleb‐related Infection study, reported that bleb‐related infection, particularly stage III, causes significant visual impairment (Yamamoto et al. ,b).…”
Section: Discussionmentioning
confidence: 53%
“…On the one hand, chemical substances, such as mitomycin C or 5‐fluorouracil, can be used to improve the results by reducing scarring reaction . The usage of these substances, however, entails a higher risk for wound healing disorders and severe infections . On the other hand, separating agents such as hyaluronate hydrogel, biodegradable collagen, or expanded polytetrafluoroethylene coatings can be used to separate the scleral flap from the lower part of the sclera to prevent scarring.…”
mentioning
confidence: 99%
“…Durch Änderung des Zugangs (fornixbasiert statt limbusbasiert) wird u. a. auch eine breitflächigere Applikation von Mitomycin C möglich und die Rate zystisch verdünnter avaskulärer Filterkissen (▶ Abb. 1) gesenkt, die häufiger zur Leckage und damit zur Blebitis neigen [10]. Eine Überfiltration mit ihren unerwünschten Nebenwirkungen wie abgeflachter Vorderkammer, Aderhautabhebung und Aderhautfalten mit Visusabfall (▶ Abb.…”
Section: Ergebnisse Der Chirurgischen Glaukombehandlungunclassified